The Effect of Succession Taxes on Family Firm Investment: Evidence from a Natural Experiment - TSOUTSOURA, MARGARITA (Journal of Finance, 2015)
ABSTRACT This paper provides causal evidence on the impact of succession taxes on firm investment decisions and transfer of control. Using a 2002 policy change in Greece that substantially reduced the tax on intrafamily transfers of businesses, I show that succession taxes lead to a more than 40% decline in investment around family successions, slow sales growth, and a depletion of cash reserves. Furthermore, succession taxes strongly affect the decision to sell or retain the firm within the family. I conclude by discussing implications of my findings for firms in the United States and Europe.